(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. The economic development of the region is determined by the resource potential and the ability to use it effectively. Among the branches of the national economy of Ukraine, the most important place is occupied by the agro-industrial complex, which forms not only a powerful export potential of the state, but also is the basis for the development of many branches of the processing industry in the country. This is especially true for Lviv region, where significant capacities for processing agricultural raw materials are concentrated, but the regional structure of foreign economic operations indicates the dominance of raw material exports. The purpose of the article. Determining the priorities of foreign economic activity of agro-industrial enterprises of Lviv region, taking into account the export potential and import needs of goods and services. Results. The positive balance of foreign trade of the agro-industrial complex of Lviv region is formed by the export of grain crops, sugar, fat and oil. At the same time, the vast majority of products are imported by the region, despite the favorable resource potential for its production. Among the priority areas of international support for the agro-industrial complex of the Lviv region, we see the implementation of experience exchange programs for the formation of an institutional environment, improving the level of management and human resources of industry enterprises, and implementing international innovation projects. In addition to organizational support, the region needs real investments in promising agricultural sectors, their infrastructure support and the creation of vertically integrated systems for integrated production and sale of finished products. Among the export priorities of foreign economic activity of agricultural enterprises are trade in products of processing enterprises, export of organic goods and use of transit potential of the region. Conclusions. Determining the priorities of foreign economic activity of the agro-industrial complex of the region will solve the problem of forming an effective structure of foreign economic operations of enterprises, taking into account regional characteristics and national interests.